Industry 4.0 solutions for building design and construction : a paradigm of new opportunities /: a paradigm of new opportunities. (2021) - Rahimian, Farzad Pour; Goulding, Jack; Abrishami, Sepehr; Seyedzadeh, Saleh; Elghaish, Faris
No abstract available